Trade liberalization and child mortality: A synthetic control method - Alessandro Olper; Daniele Curzi; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
We study the causal effect of trade liberalization on child mortality by exploiting 41 policy reform experiments in the 1960-2010 period. The Synthetic Control Method for comparative case studies allows to compare at the country level the trajectory of post-reform health outcomes of treated countries (those which experienced trade liberalization) with the trajectory of a combination of similar but untreated countries. In contrast with previous findings, we find that the effect of trade liberalization on health outcomes displays a huge heterogeneity, both in the direction and the magnitude of the estimated effect. Among the 41 investigated cases, 19 displayed a significant reduction in child mortality after trade liberalization. In 19 cases there was no significant effect, while in three cases we found a significant worsening in child mortality after trade liberalization. Trade reforms in democracies, in middle income countries and which reduced taxation in agriculture reduce child mortality more.
Keywords: Q18; O24; O57; I15; F13; F14; 330; Trade liberalization; Child Mortality; Synthetic Control Method